Individualized screening interval for prostate cancer based on prostate-specific antigen level: results of a prospective, randomized, population-based study. - Aus, G; Damber, J; Khatami, A; Lilja, H; Stranne, J; Hugosson, J (2005)
BACKGROUND: The aim of the present study was to evaluate the future cumulative risk of prostate cancer in relation to levels of prostate-specific antigen (PSA) in blood and to determine whether this information could be used to individualize the PSA testing interval. METHODS: The study included 5855 of 9972 men (aged 50-66 years) who accepted an invitation to participate in a prospective, randomized study of early detection for prostate cancer. We used a protocol based on biennial PSA measurements starting from 1995 and 1996. Men with serum PSA levels of 3.0 ng/mL or more were offered prostate biopsies. RESULTS: Among the 5855 men, 539 cases of prostate cancer (9.2%) were detected after a median follow-up of 7.6 years (up to July 1, 2003). Cancer detection rates during the follow-up period in relation to PSA levels were as follows: 0 to 0.49 ng/mL, 0% (0/958); 0.50 to 0.99 ng/mL, 0.9% (17/1992); 1.00 to 1.49 ng/mL, 4.7% (54/1138); 1.50 to 1.99 ng/mL, 12.3% (70/571); 2.00 to 2.49 ng/mL, 21.4% (67/313); 2.50 to 2.99 ng/mL, 25.2% (56/222); 3.00 to 3.99 ng/mL, 33.3% (89/267); 4.00 to 6.99 ng/mL, 38.9% (103/265); 7.00 to 9.99 ng/mL, 50.0% (30/60); and for men with an initial PSA of 10.00 ng/mL or higher, 76.8% (53/69). Not a single case of prostate cancer was detected within 3 years in 2950 men (50.4% of the screened population) with an initial PSA level less than 1 ng/mL. CONCLUSIONS: Retesting intervals should be individualized on the basis of the PSA level, and the large group of men with PSA levels of less than 1 ng/mL can safely be scheduled for a 3-year testing interval.